Impacts on Rural Livelihoods in Cambodia Following Adoption of Best Practice Health and Husbandry Interventions by Smallholder Cattle Farmers. (3rd January 2014) - Young, J. R.; O'Reilly, R. A.; Ashley, K.; Suon, S.; Leoung, I. V.; Windsor, P. A.; Bush, R. D.
Summary: To better understand how smallholder farmers whom own the majority of Cambodian cattle can contribute to efforts to address food security needs in the Mekong region, a five‐year research project investigating methods to improve cattle health and husbandry practices was conducted. Cattle production in Cambodia is constrained by transboundary animal diseases (TADs) including foot‐and‐mouth disease (FMD) and haemorrhagic septicaemia (HS) plus poor nutrition, reproduction and marketing knowledge. The project worked in six villages in Kandal, Takeo and Kampong Cham province during 2007‐12. Farmers from three 'high intervention' (HI) villages incrementally received a participatory extension programme that included FMD and HS vaccination, forage development and husbandry training. Evaluation of project impacts on livelihoods was facilitated by comparison with three 'low intervention' (LI) villages where farmers received vaccinations only. Results of knowledge, attitude and practice (KAP) and socio‐economic surveys conducted in 2012 of 120 participating farmers identified that farmer knowledge in the HI project sites exceeded LI sites on the topics of biosecurity, internal parasites, nutrition and reproduction. HI farmers adopted biosecurity practices including a willingness to vaccinate for FMD and HS at their own cost, separate sick from healthy cattle, grow and feed forages and displayed awareness of the benefits of building fattening pens. HI farmers that grew forages observed time savings exceeding two hours per day each for men, women and children, enabling expansion of farm enterprises, secondary employment and children's schooling. Logistic regression analysis revealed that farmers in the HI group significantly increased annual household income ( P < 0.001), with 53% reporting an increase of 100% or more. We conclude that improving smallholder KAP of cattle health and production can lead to improved livelihoods. This strategy should be of interest to policymakers, donors, researchers and extension workers interested in addressing TAD control, food insecurity and rural poverty in Southeast Asia.